Studi Evaluasi Program Pemberdayaan Masyarakat melalui Industri Tenun di Desa Wisata Gamplong - Julianto, Alfin; Siregar, Nelda Sari (YASIN, 2025)
This study focuses on a comprehensive evaluation of the weaving industry program in Gamplong Tourism Village using the CIPP model (Context, Input, Process, Product). A qualitative method was employed, with data collected through observation, in-depth interviews, and document analysis. Key informants were selected using purposive sampling to obtain relevant and in-depth information. The evaluation results show that, in terms of context, the weaving program benefits from strong social and cultural support as a generational heritage. The input aspect indicates the readiness of human resources and local community support for the program. In the process aspect, activities such as production, marketing, and integration with the tourism sector have been implemented as planned. Evaluation of the product aspect reveals that the weaving industry program has had a positive impact on the local economy and job creation. However, challenges remain in marketing due to market competition and limited funding for the sustainable development of the tourism village. These findings provide valuable insights for formulating strategies to strengthen the program by preserving successful elements and addressing identified weaknesses. The study recommends enhancing digital marketing capacity, strengthening partnerships, and diversifying woven products as strategic steps to support program sustainability.